2017
DOI: 10.1515/macvetrev-2016-0094
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of the Bluetongue Outbreak in Serbia

Abstract: Bluetongue, a vector-born disease caused by the Bluetongue virus (BTV) and transmitted by Culicoides biting midges, is considered to be one of the most important diseases of domestic ruminants. The first outbreak of bluetongue in Serbia was reported in 2001, when BTV serotype 9 was identified in sampled materials. In 2014, outbreak of BTV-4 in Serbia caused considerable economic losses affecting sheep, cattle and goats. During this outbreak, BTV-4 was recorded in 644 outbreaks within 49 municipalities, part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
2
0
1
Order By: Relevance
“…In Serbia, the same BTV‐4 epidemics caused economic losses affecting sheep, cattle and goats with morbidity of 0.2%, 0.06% and 0.03%, respectively. Recorded mortality in cattle, sheep and goats was 18.45% (n = 38), 48.10% (n = 1,002) and 54.17% (n = 13), respectively (Djurić et al., ).…”
Section: Assessmentmentioning
confidence: 99%
“…In Serbia, the same BTV‐4 epidemics caused economic losses affecting sheep, cattle and goats with morbidity of 0.2%, 0.06% and 0.03%, respectively. Recorded mortality in cattle, sheep and goats was 18.45% (n = 38), 48.10% (n = 1,002) and 54.17% (n = 13), respectively (Djurić et al., ).…”
Section: Assessmentmentioning
confidence: 99%
“…However, due to the fact that for 58% of the outbreaks the observation date was unknown, these results might be biased, as a result of delayed reporting and missing information. A study in Serbia which investigated the BTV-4 outbreaks at a national scale, showed similarly that the peak of the outbreak was in September and October 2014 (18). In Macedonia, the last BT outbreak was reported at the start of November 2014 and no BTV viral circulation has been detected up to the end of study period (19).…”
Section: Spread Of the Bluetongue Virusmentioning
confidence: 93%
“…В течение последних 20 лет распространение блютанга существенно изменилось в Европе. Глобальное изменение климата повлияло на появление разных серотипов вируса в географических районах выше 50º N [62].…”
unclassified